2021
DOI: 10.3389/fncel.2021.658244
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Transporter Function Is Facilitated by Converging Biology of α-Synuclein and Cholesterol

Abstract: Striatal dopamine transporters (DAT) powerfully regulate dopamine signaling, and can contribute risk to degeneration in Parkinson’s disease (PD). DATs can interact with the neuronal protein α-synuclein, which is associated with the etiology and molecular pathology of idiopathic and familial PD. Here, we tested whether DAT function in governing dopamine (DA) uptake and release is modified in a human-α-synuclein-overexpressing (SNCA-OVX) transgenic mouse model of early PD. Using fast-scan cyclic voltammetry (FCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Negative controls (without primary antibody) ensured secondary antibody specificity and pilot studies determined optimal primary antibody concentrations. Staining and expression was similar to previous studies (See Larson and Ariano, 1995 for DRD 2 ; Sun et al, 2020 for ΔFosB; and Threlfell et al, 2021 for DAT). For DRD 2 , antigen retrieval was performed prior to blocking.…”
Section: Methodssupporting
confidence: 82%
“…Negative controls (without primary antibody) ensured secondary antibody specificity and pilot studies determined optimal primary antibody concentrations. Staining and expression was similar to previous studies (See Larson and Ariano, 1995 for DRD 2 ; Sun et al, 2020 for ΔFosB; and Threlfell et al, 2021 for DAT). For DRD 2 , antigen retrieval was performed prior to blocking.…”
Section: Methodssupporting
confidence: 82%
“…Some studies indicate that the cholesterol content of brain membranes is linked with DAT-mediated dopamine neurotransmission [ 81 ]. Recently, cholesterol transporter ABCA1 was reported to be involved in the control over DAT activity [ 82 ]. It should be emphasized that the expression correlation between Snhg4 and Abca1 is one of the most statistically significant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in two alpha-synuclein deficient mouse lines, one carrying a spontaneous deletion of alpha-synuclein locus and the other a transgenic alpha-synuclein knockout, stimulated dopamine overflow was higher with a concomitant decrease in dopamine reuptake in the dorsal striatum [86]. Furthermore, human alphasynuclein-overexpressing transgenic mice, a model of early PD, demonstrate elevated dopamine uptake rates and more pronounced effects of DAT inhibitors on evoked extracellular dopamine concentrations [88]. Utilizing ex vivo slice FSCV it has been demonstrated that alpha-synuclein promotes striatal DAT function through mechanisms dependent on extracellular cholesterol, thus suggesting converging biology of alpha-synuclein and cholesterol to regulate DAT that potentially promotes vulnerability to neuronal degeneration in PD [88].…”
Section: Parkinson's Diseasementioning
confidence: 97%
“…Furthermore, human alphasynuclein-overexpressing transgenic mice, a model of early PD, demonstrate elevated dopamine uptake rates and more pronounced effects of DAT inhibitors on evoked extracellular dopamine concentrations [88]. Utilizing ex vivo slice FSCV it has been demonstrated that alpha-synuclein promotes striatal DAT function through mechanisms dependent on extracellular cholesterol, thus suggesting converging biology of alpha-synuclein and cholesterol to regulate DAT that potentially promotes vulnerability to neuronal degeneration in PD [88]. In a human alpha-synuclein-expressing mouse model of PD with macroautophagic failure in dopamine neurons, an increase in evoked extracellular concentrations of dopamine, reduction of dopamine uptake, and relieved paired-stimulus depression was found [89].…”
Section: Parkinson's Diseasementioning
confidence: 99%